제4차산업혁명시대 부동산산업의 정보기술 수용의 영향요인에 관한 연구 - 경정익(Kyung, Jung Ik); 권대중(Kwon, Dae Jung) (대한부동산학회지, 2018)
본 연구는 제4차산업혁명시대 최근 이슈가 되는 프롭테크(PropTech)의 국내 활성화를 위해서는 정보기술 도입에 따른 어떠한 전략적 가치에 중점을 두어야 하는지 그리고 환경적 측면에서는 어떠한 면을 고려하여야 하는지를 밝히고자 하는 것이다. 관련이론과 선행연구 고찰 그리고 다양한 부동산 분야 종사자의 설문조사를 통해 다음과 같은 연구결과가 도출되었다. 즉 정보기술을 비즈니스에 활용하는 실무자, 관리자, 최고경영자의 전문적 지식습득을 할 수 있는 환경조성이 필요하며, 정보기술을 도입함에 있어 산출되어 제공되는 서비스의 개선, 위기감지, 새로운 기회발견이 가능한지에 대한 면밀한 검토가 필요하다. 또한 정보기술 도입을 위해서는 매출액, 수익률 향상이 될 수 있는지 검토가 중요하다는 것이다. 그리고 정보기술 도입을 활성화하기 위해서는 법규 및 제도개선 등 공공의 노력이 중요한 요인으로 도출하였다. 본 연구는 부동산 산업이 다양한 분야의 균형된 설문조사를 통한 분석이 요구되며, 정보기술에 대한 지식이 충분히 갖추어진 응답자에 의한 기초자료 수집이 되어야 할 것이다. 또한 선행연구에서 제시한 유의한 관계를 파악하기 위해서는 보다 많은 표본을 확보하고, 통계적으로 보다 세분화하여 분석하는 것이 필요하다. This study aims to identify what strategic values should be placed on the basis of information technology introduction and what aspects should be considered in terms of the environment in order to revitalize PropFech in Korea, a recent issue of the Fourth Industrial Revolution. The following research results were derived from the related theories, the consideration of prior studies and surveys of people working in various real estate sectors. In other words, we need to create an environment in which we can acquire expertise from practitioners, managers and CEOs who utilize information technology in the business, and closely examine the improvement of services, risk detection, and new opportunities that are provided in the introduction. In addition, it is important to consider whether it can improve sales and profitability for information technology. In addition, public efforts, such as legal regulations and system improvement, were cited as important factors to revitalize the introduction of information technology. This study will require a balanced survey of the real estate industry in a variety of fields, and should be a basic data collection by respondents with sufficient knowledge of information technology. It is also necessary to obtain more samples and statistically more detailed analyses to identify the significant relationships presented in the preceding study. KCI Citation Count: 3